24 Gliflozins and ventricular function in patients affected by chronic heart failure with diabetes mellitus. (8th December 2021) - Fortunato, Martino; Mazzeo, Pietro; Correale, Michele; Paradiso, Matteo; Furore, Andrea; Fanizzi, Angela Ilaria; Tricarico, Lucia; Maiellaro, Pasquale; Pastore, Giuseppe; Alfieri, Simona; Lamacchia, Olga; Iacoviello, Massimo; et al.
Abstract: Aims: Diabetes is the most common comorbidity of HF patients. SGLT2 inhibitors has been shown to reduce hospitalization in patients with HF. The cardioprotective mechanisms of gliflozines have not been elucidated. The aim of our study was to evaluate the effect of SGLT2 inhibitors on right and left ventricular function in T2DM patients with HF. Methods and results: One hundred and fifteen consecutive outpatients with CHF and T2DM were screened in the Daunia Heart Failure Registry. Seventy-eight of them were enrolled and followed up between May 2019 and September 2020. All patients underwent conventional, TDI and strain echocardiography in an ambulatory setting, at the beginning and after 3 months of therapy with SGLT2 inhibitors. Seventy-eight consecutive outpatients with CHF and T2DM (mean age 67.4 ± 8.4 years, male: 83%) were enrolled in the study. Thirty-eight of them started the treatment with SGLT2 inhibitors, while the remaining forty continued their original therapy. After 3 months of therapy, LVEF, LVEDD, and LVESD statistically improved (respectively, from 39.68 ± 7.78% to 45.08 ± 9.04%, P : 0.001 and 57.32 ± 9.76 mm to 54.16 ± 6.54 mm, P : 0.01 and from 47.51 ± 1.58 mm to 43.24 ± 8.12, P : 0.0008). Changes in left ventricular function and dimensions were not significant in patients who did not started a therapy with SGLT2 inhibitors. There was a statistically significant reduction of E / E ′ (from 16.51 ± 22.55 to 9.73 ± 3.35, P : 0.0007) in patients with treatment with SGLT2i. Moreover, there was an improvement of right ventricular function, due to a statistically significant reduction of PAPs and increase of TAPSE (respectively, from 30.63 ± 8.80 to 24.00 ± 8.35, P : 0.008; from 19.16 ± 2.54 to 21.18 ± 2.84, P : 0.0003) and S ′ (10.42 ± 2.09 to 12.91 ± 2.50, P : 0.000) 3 months after the administration of SGLT2 inhibitors therapy vs. the control group. Conclusions: In a real-world scenario, our results showed that the treatment with SGLT-2 inhibitors in patients with CHF and diabetes is associated with an echocardiographic biventricular function improvement.